The Effect of Digital Financial Literacy and E-Commerce Adoption on the Post-Disaster Economic Resilience of Food-Sector MSMEs - Arfandi SN; Mutia Febrina Sari (Perspectives on Advanced New Generations of Global and Local Economic Horizons, 2026)
The economic resilience of Micro, Small, and Medium Enterprises (MSMEs) in the food sector following a disaster is influenced by various digital factors. This study examines the effect of digital financial literacy (DFL) and e-commerce adoption (ECA) on the post-disaster economic resilience of food-sector MSMEs in West Sumatra Province, Indonesia. A quantitative approach with multiple linear regression analysis was employed, using a sample of 150 respondents drawn through purposive sampling. Validity was confirmed via Pearson correlation and confirmatory factor analysis (loading factor > 0.70), and reliability was established through Cronbach's Alpha (α > 0.70). Classical assumption tests normality (Kolmogorov-Smirnov, p = 0.200), heteroscedasticity (Glejser, p > 0.05), and multicollinearity (VIF = 1.381) were all satisfied. Results indicate that DFL (β = 0.396; t = 5.817; p < 0.001) and ECA (β = 0.391; t = 5.559; p < 0.001) each significantly and positively influence economic resilience. Simultaneously, both variables explain 61.4% of the variance in economic resilience (R² = 0.614; F = 117.43; p < 0.001). These findings suggest that strengthening digital financial literacy and promoting e-commerce adoption are critical strategies for rebuilding MSME economic capacity in disaster-prone regions.